2021
DOI: 10.3389/fmed.2021.573601
|View full text |Cite
|
Sign up to set email alerts
|

“Patient Comfort Can Be Sacrificed for Patient Safety”—Perception and Practice Reported by Critical Care Nurses Toward Physical Restraints: A Qualitative Descriptive Study

Abstract: Aim: The aim of the study was to explore the perception and practice of physical restraints used by critical care nurses.Design: A qualitative descriptive design was used.Method: From December 2019 to May 2020, a one-to-one, semi-structured in-depth interview with 10 critical care nurses from two intensive care units in a tertiary general hospital with 3,200 beds in China was conducted using the method of purposeful sampling. The data were analyzed using inductive thematic analysis.Findings: The perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Family presence may decrease PRs use or may increase their use for critically ill patients ( 14 , 15 ). In our previous qualitative studies ( 16 , 17 ), an inextricable link was also found between PRs and unplanned extubation, MV, pain, agitation/sedation, delirium, and family engagement. Therefore, we proposed a hypothesis that interventions that could decrease the incidence of unplanned extubation, delirium, agitation, and the duration of MV or were conducive to family-centered care would probably decrease PRs use.…”
Section: Introductionmentioning
confidence: 64%
“…Family presence may decrease PRs use or may increase their use for critically ill patients ( 14 , 15 ). In our previous qualitative studies ( 16 , 17 ), an inextricable link was also found between PRs and unplanned extubation, MV, pain, agitation/sedation, delirium, and family engagement. Therefore, we proposed a hypothesis that interventions that could decrease the incidence of unplanned extubation, delirium, agitation, and the duration of MV or were conducive to family-centered care would probably decrease PRs use.…”
Section: Introductionmentioning
confidence: 64%
“… 39 Our previous study found that nurses believed that physical restraints could efficiently prevent patients from having an unplanned extubation. 25 In this study, critical care clinicians indicated that unplanned extubation was highly likely to cause medical disputes. Overall, physical restraints avoided medical disputes by preventing patients from having unplanned extubation.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous analysis, 25 we also found that critical care nurses knew the negative influence of physical restraints on patients, but they still commonly used physical restraints. The prevention of unplanned extubation seemed to be the driving reason behind physical restraints use.…”
Section: Introductionmentioning
confidence: 72%
“…Critical care nurses' intention of physical restraint is to ensure patient safety and maintain job security. Some studies reported that patient safety is the primary trigger (Canzan et al, 2021; Cui, Qiu et al, 2021; Dolan & Dolan, 2017; Langley et al, 2011; Perez et al, 2021; Salehi et al, 2020; Shen et al, 2021; Via‐Clavero et al, 2019; Wang et al, 2015; Yang & Li, 2017). Interruption or removal of invasive monitoring and therapeutic devices were identified as a significant threat to patient safety.…”
Section: Resultsmentioning
confidence: 99%
“…However, various determinants motivate critical care nurses to decide the physical restraint use, including patient status, nurse characteristics, other caregivers' negative attitudes towards physical restraint, and organisational barriers. Critical care nurses described patient status as the primary determinant of physical restraint use (Canzan et al, 2021; Cui, Qiu et al, 2021; Shen et al, 2021; Wang et al, 2018; Via‐Clavero et al, 2019; Dolan & Dolan, 2017; Wang et al, 2015). Patients who are unconscious, agitated, and have life‐sustaining tubes are considered at high risk for needing physical restraint: “Patients experiencing agitation or delirium, and/or non‐cooperative patients should be firmly restrained and not allowed to move at all (Cui, Qiu et al, 2021) .” “…you'll find that they are more often used in someone who's intubated, plus or minus sedation, and it's basically to prevent that extubation (Perez et al, 2021) .”…”
Section: Resultsmentioning
confidence: 99%